Increasing Students' Awareness Of The Dangers Of Online Loans And Online Gambling Through Education And Socialization - umuri, Khairil; Gunawan, Eddy; Sari, Nurma; Amri, Amri; Syahriyal, Syahriyal; Afandi ZT, Fitrah; Muftahuddin, Muftahuddin (Jurnal Pengabdian Bakti Akademisi, 2024)
The development of digital technology has brought various benefits, but it also poses significant risks to the well-being of individuals, especially the younger generation. The phenomenon of online loans and online gambling poses a serious threat among students, who often lack financial literacy and awareness of digital risks. This research aims to raise students' awareness of the dangers of online lending and online gambling through an education and socialization program at SMAN 1 Sigli, Aceh. The program was implemented using the Participatory Action Research (PAR) method, which includes four phases: identification, needs determination, intervention, and evaluation. The results showed that after participating in the program, there was a significant increase in students' understanding of the risks of online loans and online gambling, as well as a change in attitudes towards both issues. In addition, teachers involved in the program reported increased confidence in delivering related materials to students. These findings suggest that an interactive and comprehensive educational approach can be effective in protecting students from the risks of online lending and online gambling. Recommendations for further development include implementing similar programs in other schools, developing more comprehensive educational materials, and increasing parental and community involvement in prevention efforts. This research contributes to the development of Islamic financial literacy, digital risk awareness, and supports the achievement of the Sustainable Development Goals (SDGs).